PENGEMBANGAN PERANGKAT PENILAIAN KINERJA (PERFORMANCE ASSESSMENT) BERBASIS KURIKULUM 2013 PADA PEMBELAJARAN KIMIA KELAS XI - Diartha -; Wildan -; Muntari - (Jurnal Penelitian Pendidikan IPA, 2017)
This development research aimed to produce performance assessment instrument on chemistry learning for XI grade, descibe for characteristics, and validity tests. This research development used Dick and Carey’s model. The products consists of acid-base proved into worksheet, evaluation of indicators, direction of usage, sheet of observation, rubric of assessment, assessment of conversion, and value of recapitulation. Validation’s data of Aiken were 0,60 for unit one, unit two for 0,60, and 0,66 for unite three means valid. The data of experiment were 84% for suitability, 87% for simplicity, and 84% for usefullness. Application’ data for suitability, simplicity, and usefullness were 84%, 86%, and 84% respectively. Upper validity correlation table within 5% of significant level and reability inter-raters were 0,76 for unit one and 0,75 for unit two. Application of assessment’s instrument were positively responded by students. Therefore, instrument of assessment in 2013 curriculum-based stated applicable to be implemented in learning process.Keywords: Performance assessment-instrument, Applicable, Chemistry  learning